Area and volume of the pharyngeal airway in surgically treated unilateral cleft lip and palate patient: A cone beam computed tomography study - Shailendra Singh Rana; Ritu Duggal; Om Prakash Kharbanda (Wolters Kluwer Medknow Publications, 2015)
Background: Area and volume of the pharyngeal airway in surgically treated unilateral cleft lip and palate (UCLP) patient: A cone beam computed tomography (CBCT) study. Context: Surgical repair of cleft causes restriction of maxillary growth and mid face but the effect of this reduced growth on volume of the pharyngeal airway has not been investigated thoroughly. Aims: The aim of the study was to assess the area, volume and smallest cross-sectional area of the pharyngeal airway in individuals with UCLP using CBCT and compare with age and sex matched noncleft controls. Settings and Design: Retrospective study. Materials and Methods: The study was carried out on 20 surgically treated UCLP patients and compared with 40 normal non cleft subjects with Class I skeletal relation within age group of 7-14 years. CBCT image processing and analysis were performed using Dolphin Imaging software (11.7 version premium; Dolphin Imaging and Management Solutions, Chatsworth, Calif) and volumetric rendering was done for airway analysis. Statistical Analysis Used: All statistical analyses were performed with SPSS software (version 15.0J for Windows; SPSS, Inc., Chicago, IL). An independent sample t-test was used to determine the significance of the difference between the means. Results: No significant difference was found in the area and volume of nasopharynx, oropharynx, hypopharynx, total pharyngeal volume (P = 0.86) and minimum axial area (P = 0.69) of the pharynx between the groups. Conclusions: Using CBCT, this study found that there was no significant difference in the pharyngeal area and volume between UCLP and noncleft groups. Further investigations are necessary to clarify the relationship between pharyngeal structure and airway function in patients with CLP.